A dangerous breed : a novel - Hamilton, Glen Erik (Hamilton, Glen Erik. Van Shaw novel, 2020)
An invitation addressed to his long-dead mother sparks Van Shaw's curiosity about the woman he barely knew. As he digs into young Moira Shaw's past, he uncovers startling details about her life, including her relationship to a boy named Sean Burke, a boy Moira may have been seeing when she became pregnant. Could this Burke be the biological father who abandoned Van before he was born? Although Van knows all too well that some doors shouldn't be opened, he decides to investigate the man only to discover that Burke has an even darker family history than Van's own. But Van's got more immediate problems. His friend Hollis is in a jam, and helping him out accidentally steers Van into the path of a master extortionist named Bilal Nath. Nath demands that the talented thief mastermind a daring heist targeting a Seattle biotechnology firm, or the blackmailer will destroy the lives of people Van loves. With Bilal Nath coercing him into a possible act of domestic terrorism, Van turns to his formidable crew of lawbreaking friends, including Hollis, Big Will Willard, and Willard's sly and seductive niece Elana, for help. Yet even this team may not be enough. To outwit a brilliant sociopath, Van might just need a cold-blooded killer, a criminal whose blood may run through his own veins.